Pengaruh beban kerja dan lingkungan kerja terhadap kinerja pegawai melalui Work-Life Balance sebagai variabel mediasi - Panjaitan, Dicky Julius; Komari, Nurul; Daud, Ilzar (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2025)
In the midst of globalization and intense competition, organizations encourage employees to work harder, but this risks disrupting Work-Life Balance. This study aims to determine the effect of workload and work environment on performance, as well as the role of Work-Life Balance as a mediating variable at BAPENDA West Kalimantan Province. The approach used is quantitative, with primary and secondary data analyzed using SmartPLS 3.3.2. A Likert scale of 1-5 was used to measure statement items. The results showed that workload has a negative and significant effect on employee performance. This shows that the higher the perceived workload, the employee performance tends to decrease. In addition, Work-Life Balance significantly mediates (partially) the positive effect of work environment on performance. This finding confirms the importance of creating a work environment that supports work-life balance to improve the performance of ASN employees.